The effect of forest cutting on the quality of groundwater in large aquifers in Finland - Rusanen, K.; Finér, L.; Antikainen, M.; Korkka-Niemi, K.; Backman, B.; Britschgi, R. (Boreal Environment Research Publishing Board, 2024)
The effects of forest cuttings on the level of the groundwater table and the quality of groundwater in large aquifers in Finland were studied by interpreting the long-term data from three groundwater monitoring stations together with information about the forest management history. Groundwater nitrate concentrations increased after clear-cuttings and thinnings for several years after the operations. However, the nitrate concentrations remained low (< 2 mg l–1) even after the treatments. None of the changes in the groundwater level or in the other studied variables (electrical conductivity, alkalinity, pH, ammonium, chloride, sulphate, sodium, potassium, calcium and magnesium) could be attributed to the forestry operations.